2022
DOI: 10.3390/jof8050513
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Arbuscular Mycorrhizal Fungus Funneliformis mosseae on the Physiological and Defence Responses of Canna indica to Copper Oxide Nanoparticles Stress

Abstract: Copper oxide nanoparticles (nano-CuO) are recognized as an emerging pollutant. Arbuscular mycorrhizal fungi (AMF) can mitigate the adverse impacts of various pollutants on host plants. However, AMF’s mechanism for alleviating nano-CuO phytotoxicity remains unclear. The goal of this study was to evaluate how AMF inoculations affect the physiological features of Canna indica seedlings exposed to nano-CuO stress. Compared with the non-AMF inoculated treatment, AMF inoculations noticeably improved plant biomass, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Furthermore, the amino acids glutamine and leucine have been reported to function as signaling molecules and regulate essential stress-responsive genes [ 63 , 64 ]. Inoculating with AMF under abiotic stress may alleviate the stress by synthesizing organic acids, secondary metabolites, and phytohormones, and via other pathways [ 60 , 65 ]. Significantly upregulated expression of organic acids, such as citric acid, tartaric acid, ascorbic acid, ribonic acid, and hexaric acid, which sequester the soil and bind the toxicity of Cd in the soil, can minimize the uptake of Cd by plants and enhance the uptake of essential nutrients by plants [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the amino acids glutamine and leucine have been reported to function as signaling molecules and regulate essential stress-responsive genes [ 63 , 64 ]. Inoculating with AMF under abiotic stress may alleviate the stress by synthesizing organic acids, secondary metabolites, and phytohormones, and via other pathways [ 60 , 65 ]. Significantly upregulated expression of organic acids, such as citric acid, tartaric acid, ascorbic acid, ribonic acid, and hexaric acid, which sequester the soil and bind the toxicity of Cd in the soil, can minimize the uptake of Cd by plants and enhance the uptake of essential nutrients by plants [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inoculation with AMF had a limiting effect on the uptake of Al in rice, and inoculation with AMF could provide new mechanisms for the exclusion and detoxification of Al, such as metal immobilization in extra- and intraradical mycelia ( Alotaibi et al., 2021 ). Moreover, AMF regulates the expression of host genes related to metal transport ( Luo et al., 2022 ). Overall, inoculation with AMF affects the uptake of elements from the soil by rice.…”
Section: Discussionmentioning
confidence: 99%
“…These genes may also have been affected by inoculation with Fm. Studies have shown that AMF can affect the expression of genes related to the plasma membrane and cell wall activities, and Fm can positively affect plant cellular components, biological process, and molecular function, and the expression of genes related to the transport of metal ion transports in plants ( Lu et al., 2020 ; Moradi et al., 2020 ; Luo et al., 2022 ). Therefore, the application of Fm combined with Se can affect the expression of genes related to the uptake of metal ions and Se metabolism (glutathione metabolism).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [ 24 , 25 , 26 , 27 ] have indicated that the inoculation of arbuscular mycorrhizal fungi (AMF) can have significant effects on plants, including increased absorption and utilization of mineral nutrients, altered uptake and transport of heavy metals, and alleviation of the adverse effects of heavy metal stress, thereby helping to improve the tolerance of host plants to heavy metals. Specifically, AMF colonization can enhance the arsenic resistance of either resistant or non-resistant plants grown in arsenic-contaminated soils by reducing arsenic biotoxicity [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%